Inter-Korean Economic Cooperation and a Role of Trade in It - Sapelnikova, Anna (2017)
This diploma thesis focuses on the economic cooperation between North Korea and South Korea. This topic is essential to study because not only does it illustrate significant historical affairs, such as division of one nation and a fight for independency, but it also has a serious impact on the global economy. The topic is chosen for several complex reasons. First of all, the issue of South-North relationship is quite interesting in and of itself. Secondly, the economic potential of the East Asian region is exponential. The rising importance of Eastern Asia in the global economy became self-evident. The purpose of the diploma thesis is to study Inter-Korean economic cooperation, determine the role of trade in it, and to find answers for the research questions using quantitative analysis within methodology.